Characterization of Poly Lactic Acid (PLA) Based on PEG-200 Modification of Clay-CaCO3 as Subtitution to LDPE Coating Paper - Rohmah, Aisyah Alifatul Zahidah; Widjaja, Tri; Sari, Citra Yulia; Fajrin, Alifah Nur Aini (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
Plastics play a central role in daily life due to their lightweight nature, mechanical strength, low cost, and durability. Nevertheless, their environmental impact is significant, as they contribute to pollution and global warming. Polylactic Acid (PLA) has gained attention as a biodegradable alternative to conventional LDPE plastics. Although environmentally friendly, PLA exhibits inherent limitations such as brittleness and insufficient toughness, which restrict its broader application. To overcome these drawbacks, plasticizers like Polyethylene Glycol (PEG) 200 and reinforcing agents such as clay and calcium carbonate (CaCO₃) are added to enhance its mechanical performance. This research aims to investigate how these additives affect the resulting film properties. The bioplastic film was produced using a solvent casting method with chloroform as the solvent. The mixture was stirred at ambient temperature for six hours, then cast in a single step into a closed mold and allowed to rest overnight to form a film. The resulting film had a white appearance, slight transparency, and a smooth, slippery surface. Compared to films produced using a layered pouring approach, those formed via the one-pour technique exhibited superior thickness and mechanical strength. To characterize the effects of the additives, several analytical methods were employed: X-Ray Diffraction (XRD) to analyze crystallinity, Thermogravimetric Analysis (TGA) to assess thermal stability, Fourier Transform Infrared Spectroscopy (FTIR) to identify functional groups and chemical bonds, and Dynamic Mechanical Analysis (DMA) to determine mechanical properties such as tensile strength, Young’s modulus, and elongation at break. Surface morphology was further examined using Scanning Electron Microscopy (SEM). The most favorable results were observed in the composition containing 80% PLA, 10% PEG, 5% CaCO₃, and 5% clay. This formulation yielded a crystallinity of 96.71%, a decomposition temperature of 366.22 °C, elongation at break of 12.98%, Young’s modulus of 56.77 MPa, and a tensile strength of 1.25 MPa. These findings suggest that the film has strong potential as a coating material to replace LDPE.